Postać diabła Boruty w „Baśni o diable Borucie” Artura Oppmana - Warda, Anna (Diabeł Boruta w dawnej kulturze polskiej, 2021)
The article attempts to discuss the figure of the devil Boruta in The fairy tale about the devil Boruta (1926). The author of this work is the poet of Young Poland and the interwar period, publisher, ethnologist and folklorist – Artur Oppman (1867–1931). The fairy tale was published in Oppmana’s collection entitled The Polish enchanted world and very clearly refers in terms of content to one of the two accounts of the devil Boruta, included in the collection of Kazimierz W. Wójcicki Legends, ancient stories and novels of the Polish people and Rus (1837).Artur Oppman’s fairy tale about the devil Boruta is an interesting example of a literary fairy tale in which narrative prose is combined with a poem. In contrast to the stylistically and linguistically neutral legend of Boruta in Wójcicki’s collection, Oppman’s fairy tale abounds in various linguistic and stylistic means, and the narrative has a playful, humorous and even ironic tone. The author also devoted more attention to the psychological side of Boruta than Wójcicki.